2022
DOI: 10.3389/fragi.2022.1077302
|View full text |Cite
|
Sign up to set email alerts
|

Impact of impaired cerebral blood flow autoregulation on cognitive impairment

Abstract: Although the causes of cognitive impairment are multifactorial, emerging evidence indicates that cerebrovascular dysfunction plays an essential role in dementia. One of the most critical aspects of cerebrovascular dysfunction is autoregulation of cerebral blood flow (CBF), mainly mediated by the myogenic response, which is often impaired in dementia individuals with comorbidities, such as diabetes and hypertension. However, many unsolved questions remain. How do cerebrovascular networks coordinately modulate C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 147 publications
1
6
0
Order By: Relevance
“…Brain hypoperfusion could be attributed to impaired cerebral hemodynamics, BBB leakage, and NVU dysfunction. 4,61 We found that the MR of the MCA and PA was intact in AD rats at 3 months of age, similar to what was seen in WT rats. AD rats started to lose the vasoconstrictive response to pressures at 4 months in both the MCA and PA.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Brain hypoperfusion could be attributed to impaired cerebral hemodynamics, BBB leakage, and NVU dysfunction. 4,61 We found that the MR of the MCA and PA was intact in AD rats at 3 months of age, similar to what was seen in WT rats. AD rats started to lose the vasoconstrictive response to pressures at 4 months in both the MCA and PA.…”
Section: Discussionsupporting
confidence: 77%
“…Changes in cerebral VSMC functional contractility could affect the MR of cerebral vasculature and CBF autoregulation associated with AD/ADRD 57,61,62 . We compared the contractile capability of VSMCs isolated from MCAs of AD and WT rats.…”
Section: Resultsmentioning
confidence: 99%
“…This ensures prevention of high pressure reaching the distal microcirculation, protecting against the detrimental effects of rapid changes in blood pressure, enabling the endothelium to locally regulate blood flow at the microvascular level ( Toth et al, 2017 ). Impairment of cerebral autoregulation, seen in comorbidities commonly associated with vascular cognitive impairment and dementia (i.e., hypertension, diabetes) may also contribute to impairment of NVC due to hypoperfusion or elevated arterial pressure in the distal microcirculation, potentially causing CSVD pathologies of ischemic lesions and microbleeds, respectively ( Wang et al, 2022 ). Moreover, CSVD is associated with impaired NVC ( Moretti and Caruso, 2020 ) and is strongly linked to COVID-19, as is evidenced in this systematic review.…”
Section: Discussionmentioning
confidence: 99%
“…1 Importantly, emerging research suggests a connection between vascular aging and neurodegenerative conditions like AD/ADRD. 49 The compromised blood flow to the brain due to vascular aging may play a role in the development and progression of cognitive decline and neurodegeneration. 3, 33 Understanding the intricate relationship between vascular aging, hemodynamics, and neurological health is crucial for developing targeted interventions to mitigate the risks associated with aging and promote overall vascular and cognitive well-being.…”
Section: Discussionmentioning
confidence: 99%